2024
DOI: 10.1111/jpn.13941
|View full text |Cite
|
Sign up to set email alerts
|

Dietary pterostilbene exerts potential protective effects by regulating lipid metabolism and enhancing antioxidant capacity on liver in broilers

Licong Zhang,
Jingyang Zhang,
Haoran Zang
et al.

Abstract: Intensive breeding of broilers met the increasing demands of human for broiler products, but it raised their increased susceptibility to various stressors resulting in the disorder of lipid metabolism. Pterostilbene, the methoxylated analogue of resveratrol, exhibits astonishing functions of antioxidant, anti‐inflammatory and glycolipid regulatory. The study aimed to elucidate the protective effects of pterostilbene on broiler liver and to explore the potential mechanisms. A total of 480 one‐day‐old male Arbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…These findings suggest that HE, OE, and ZE had a hepatoprotective potential against AFB1-induced oxidative stress and its associated pathogenesis. These results align with the well-established role of natural plant products in treating and preventing chronic diseases, including liver disorders [61][62][63]. In particular, Z. multiflora, O. dhofarense, and H. bacciferum have a wide medicinal application [64].…”
Section: Discussionsupporting
confidence: 81%
“…These findings suggest that HE, OE, and ZE had a hepatoprotective potential against AFB1-induced oxidative stress and its associated pathogenesis. These results align with the well-established role of natural plant products in treating and preventing chronic diseases, including liver disorders [61][62][63]. In particular, Z. multiflora, O. dhofarense, and H. bacciferum have a wide medicinal application [64].…”
Section: Discussionsupporting
confidence: 81%
“…Almost all phenols can act as lipid peroxidation antioxidants because they scavenge the chain-carrying lipid peroxyl radicals [76,77]. Rudrapal et al [78] mentioned some phenolic compounds that act against the accumulation of lipid peroxidation products including quercetin, which we found in our extracts.…”
Section: -Determination Of Tissue Proteinsmentioning
confidence: 52%
“…Previous studies have demonstrated the attractive preventive and therapeutic properties of PTE in a range of inflammation-related diseases [27][28][29][30]. Our previous research showed that compared with the control group, PTE supplementation increased final body weight (FBW), with significant improvements observed in the PTE 200 and PTE 400 groups, the PTE 200 , PTE 400 , and PTE 600 groups showed significant increases in average daily gain (ADG) [31]. However, the role of PTE in improving organism immunity and intestinal health in broilers remains unclear.…”
Section: Discussionmentioning
confidence: 98%